PEMANFAATAN BUBUR BUAH JAMBU BIJI PUTIH DAN BUBUR BUAH PEPAYA DALAM PEMBUATAN FRUIT LEATHER - Sheilla Primawidya N. F; Faizah Hamzah; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The study was purposed to get the best combination of white guava puree and papaya puree in the making fruit leather. The research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications. The treatments were JP0 (90% white guava puree:10% papaya puree), JP1 (80% white guava puree:20% papaya puree), JP2 (70% white guava puree:30% papaya puree), JP3 (60% white guava puree:40% papaya puree) and JP4 (50% white guava puree:50% papaya puree).  The data obtained were analyzed statistically using ANOVA and DNMRT at 5%.  The research showed that white guava puree and papaya puree significant on water content, ash content, degree of acidity (pH), crude fiber content, sensory evaluation for colour, flavour, texture, and overall assessment, but non significant on total sugar content and sensory evaluation for taste of fruit leather. The best treatment of fruit leather from this research is JP4 which have water content 15.99%, ash content 0.80%, degree of acidity (pH) 4.48, crude fiber content 3.49%, total sugar content 55.07%, orange colour (score 1.97), papaya flavour (score 2.27), sweetness taste (score 3.67), the texture was springy       (score 3.80), and overall assesment of fruit leather was  preferred by the panelist. Keywords: fruit leather, white guava puree, and papaya puree.